Intuitive stroke coloring - Zhang, Zhuyan (Nanyang Technological University, 2023)
Vector graphics are widely used as a creative tool in logos, posters, and many art forms where scaling without damaging quality is needed. Brushstrokes are important building blocks of vector graphics, used extensively in computer-generated calligraphic lettering and painting. Hock Soon Seah et al. introduced eXpressive B-Spline Curves (XBSC) to allow more expressive coloring and finer width control along the stroke. However, the process involved in generating the artwork is very troublesome. To address this issue, a desktop application called "eXpressiveDrawing" was created.